Pour une définition de la notion de minorité linguistique : les difficultés du vague - Christian Bassac; Joan Busquets; Victor Guset; Antoine Pascaud; Alain Viaut (Lengas)
In this paper we try and provide a definition of the notion of minorité linguistique (“linguistic minority”). The main conceptual difficulty attached to this notion arises from the vagueness of the noun minority. There is a wide range of definitions of this word sometimes varying from country to country (as there may exist several ethnic or linguistic groups defined by specific features within a given state), and consequently any a priory definition of the notion is impossible.We then chose to concentrate on the use of this term in context and built our own corpus for this purpose. Our analysis is then a semantic analysis of vagueness based on the extension of the sequence minorité linguistique. We analyze the various (mainly) adjectival modifiers that both limit the extension of this sequence and provide a heuristic allowing us to sketch out a classification of langues minoritaires (“minority languages”). In spite of the vagueness of the term, this classification also provides an explanatory account of why the equivalent of the term in other languages may recover different realities (for instance, minoranza linguistica in Italian).